Dribbling Skill Levels of Students at Al-Khairat Punggalaku Islamic Junior High School - Muh. Ilham Hafid; Gufran Asyahri; La Ode Abdul Razak (Journal of Physical Education and Health Science, 2025)
The purpose of this study was to determine the dribbling skill levels of students at Al-Khairat Punggalaku Islamic Junior High School. This study employed a descriptive quantitative research design. The participants consisted of 21 junior high school students, selected using a total sampling technique. Data were collected using a soccer dribbling skill test, and the results were analyzed using descriptive statistics, including mean, standard deviation, frequency, and percentage. The results showed that the mean dribbling score of students was 14.71 with a standard deviation of 1.68. Based on the established classification criteria, 3 students (14.28%) were categorized as having good dribbling skills, 12 students (57.14%) were in the moderate category, 4 students (19.06%) were in the poor category, and 2 students (9.52%) were in the very poor category. The majority of students were classified in the moderate skill level. In conclusion, the dribbling skills of students at Al-Khairat Punggalaku Islamic Junior High School are predominantly at a moderate level. These findings indicate the need for more structured and targeted training programs to improve students’ soccer dribbling skills in physical education learning